Comparison of Two Commercial Concentrates on Carcass Percentage and Internal Organs of Broiler Chickens - Bagas Fajar Firmansyah; Sri Sukaryani (Jurnal Biologi Tropis, 2026)
Commercial concentrates have different nutrient formulations, which may potentially affect body tissue growth and the development of internal organs in broiler chickens, ultimately influencing the percentage of carcass parts and internal organs. This study aimed to determine the effect of feeding two different types of commercial concentrates on the percentage of carcass parts and internal organs of broiler chickens. The experimental design used was a Completely Randomized Design with a one-way pattern consisting of three treatments and four replications. The treatments were P1: 100% commercial concentrate A; P2: 100% commercial concentrate B; and P3: 50% commercial concentrate A + 50% commercial concentrate B. The observed variables included the percentages of thigh, wing, and breast parts, as well as the percentages of heart, gizzard, and liver. The obtained data were statistically analyzed using analysis of variance (ANOVA), and when significant differences were detected, Duncan’s Multiple Range Test was applied. The results showed that the percentages of breast and thigh parts among P1, P2, and P3 did not differ significantly; however, the percentage of wing parts in P1 was significantly lower than in P2 and P3. The percentages of heart and liver in P1, P2, and P3 did not show significant differences, whereas the gizzard percentage in P1 was significantly different compared to P3. It can be concluded that feeding two different types of commercial concentrates significantly affected the percentages of wing and gizzard parts but did not significantly affect the percentages of breast, thigh, heart, and liver.